Building Self-Confidence in Elementary School Civic Education Learning - Luciana Giri Noviasafitri; S Sutama (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: There are three objectives of this study. 1) To describe the habit of daring to act in activities. 2) To describe the habit of making decisions without hesitation. 3) To explore the habit of expressing ideas in Civic Education learning. Methodology: This type of research uses qualitative ethnography, data collection through interviews, observation, and document analysis. Results: The results show that teachers and students consider creativity as an important aspect of Civic Education learning, where discussion, value reflection, and idea expression activities are proven to increase courage, independent thinking, and the ability to respect other people's opinions, while also making students more confident and actively involved in the learning process. Applications/Originality/Value: This study shows the practical benefits of fostering creativity in civic education learning, where discussion, reflection, and idea expression strategies can foster courage, independent thinking, and mutual respect, making them relevant for developing students' character and creativity.